Effects of MEK inhibitors GSK1120212 and PD0325901 in vivo using 10‐plex quantitative proteomics and phosphoproteomics. Issue 2 (18th October 2014) - Paulo, Joao A.; McAllister, Fiona E.; Everley, Robert A.; Beausoleil, Sean A.; Banks, Alexander S.; Gygi, Steven P.; Pandey, Akhilesh; Moran, Michael F.
<x xml:space="preserve">Abstract</x> Multiplexed isobaric tag based quantitative proteomics and phosphoproteomics strategies can comprehensively analyze drug treatments effects on biological systems. Given the role of mitogen‐activated protein/extracellular signal‐regulated kinase (MEK) signaling in cancer and mitogen‐activated protein kinase (MAPK)‐dependent diseases, we sought to determine if this pathway could be inhibited safely by examining the downstream molecular consequences. We used a series of tandem mass tag 10‐plex experiments to analyze the effect of two MEK inhibitors (GSK1120212 and PD0325901) on three tissues (kidney, liver, and pancreas) from nine mice. We quantified ∼6000 proteins in each tissue, but significant protein‐level alterations were minimal with inhibitor treatment. Of particular interest was kidney tissue, as edema is an adverse effect of these inhibitors. From kidney tissue, we enriched phosphopeptides using titanium dioxide (TiO2) and quantified 10 562 phosphorylation events. Further analysis by phosphotyrosine peptide immunoprecipitation quantified an additional 592 phosphorylation events. Phosphorylation motif analysis revealed that the inhibitors decreased phosphorylation levels of proline‐x‐serine‐proline (PxSP) and serine‐proline (SP) sites, consistent with extracellular‐signal‐regulated kinase (ERK) inhibition. The MEK inhibitors had the greatest decrease on the phosphorylation of two proteins, Barttin and Slc12a3, which have roles in ion transport and fluid balance. Further studies will provide insight into the effect of these MEK inhibitors with respect to edema and other adverse events in mouse models and human patients.